The consumption of work: representations and interpretations of the meaning of work at a UK university - Chertkovskaya, Ekaterina; Korczynski, Marek; Taylor, Scott (Sage, 2017)
This paper focuses on representations of the nexus of work, meaning and consumption as experienced by university students. We develop an empirically based argument that the meaning of work is being constructed as an object of consumption on a British university campus. We suggest that this indicates two key changes in representations of the meaning of work. First, there is a significant shift in the social construction of orientations to work towards what we term ‘consumption of work’. Second, we argue that this new social construction is made up of three dimensions: consumption of an idealised image of work, consumption through specific work processes and consumption of self-development opportunities at work. We conclude by suggesting ways in which this argument could be researched further.